Effects of Electrode Movements on Smaw Welding to The Quality of ST-37 Steel Welds - Triwibowo, Nur Akhmad; Supriatna, Eka (Institut Teknologi Dirgantara Adisutjipto, 2019)
Many factors affect the welding results including electrode movement, welding current and electrode type. This study aims to determine the effects of electrode movements on SMAW welding to the quality of ST-37 steel welds. The quality reviewed includes microstructure, tensile strength, yield stress and weld defects. The study used ST 37 Steel with thickness 10 mm and a size of 100 mm x 200 mm, open V seam with an angle of 600 degree. E 7016 series electrodes had a diameter of 3.2 mm. Welding current 90-92 amperes, polarity DC +, welding voltage 25 volts and travel speed 8-10 cm / minute. Electrode movements variations include straight, zig-zag and spiral movement. The results showed that the micro structure of the Acicular Ferrite (AF) on the electrode spiral movement looks uniform, tight, dominates the area, the spiral movement of the electrode provides the highest tensile strength and the highest yield strength and the electrode spiral movement does not produce welding defects